The influence of urease and nitrification inhibitor on loss of N and oil palm harvest in peat - Aldy Slamet Riyadi; Eka Tarwaca Susila Putra; Eko Hanudin (Jurnal Ilmu Pertanian, 2020)
Oil palm is one of intensively planted in Indonesia, large-managed for industrial oil palm. This study aimed to know the influences of urease and nitrification inhibitor on loss of N and oil palm harvest in peat. The research was conducted at Sukamandang Village Coconut Plantation, Seruyan Tengah District, Seruyan Regency, Central Kalimantan Province. The research used a single factor of field experimental method with Randomized Completely Block Design (RCBD). Urea and ZA fertilizer were used in this study with the following treatment: N0= Without N, N1= Urea (195 kg.ha-1 N), N2= Urea + 0.12% NBPT-NPPT (195 kg.ha-1 N), N3= Urea (156 kg.ha-1 N), N4= Urea + 0.12% NBPT-NPPT (156 kg.ha-1 N), N5= Ammonium Sulfate (427 kg.ha-1 N), N6= Ammonium Sulfate + 0.8% DMPP (427 kg.ha-1 N), N7= Ammonium Sulfate (324 kg.ha-1 N), N8= Ammonium Sulfate + 0.8% DMPP (324 kg.ha-1 N). The research result indicated that the use of NBPT and DMPP inhibitors did not affect N levels in the leaves and the free fatty acids. Urea + NBPT treatment had no N loss for about 30%–50% which was lower than urea without N, whereas ammonium sulfate + DMPP had smaller N loss than all treatments without N fertilization. Fertilization using urea + NBPT and ammonium sulfate + DMPP increased the production of FFB and yield of oil palm.